2014
DOI: 10.1016/j.ijnonlinmec.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Extended models of non-linear waves in liquid with gas bubbles

Abstract: In this work we generalize the models for nonlinear waves in a gas-liquid mixture taking into account an interphase heat transfer, a surface tension and a weak liquid compressibility simultaneously at the derivation of the equations for nonlinear waves. We also take into consideration high order terms with respect to the small parameter. Two new nonlinear differential equations are derived for long weakly nonlinear waves in a liquid with gas bubbles by the reductive perturbation method considering both high or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…We seek for solutions of (20) assuming that η is a polynomial in u. In this way we find infinitesimals which are presented in Table 1, where c i , i = 6, .…”
Section: Nonclassical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We seek for solutions of (20) assuming that η is a polynomial in u. In this way we find infinitesimals which are presented in Table 1, where c i , i = 6, .…”
Section: Nonclassical Methodsmentioning
confidence: 99%
“…In Refs. [19,20] it was shown that the Burgers equation with high order corrections can be used for the description of nonlinear waves in a liquid with gas bubbles. This equation has the form [19,20]: u t + αuu x − µu xx = ε (2µα 2 + µα + ν)uu xx + (2µα 1 + µα + ν)u…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exact solutions (49) and (51) are the solitary wave solutions in the form of kinks. We can look for the periodic solutions of equation (36) if we apply the method developed in works [50][51][52].…”
Section: Painlevé Analysis and Exact Solution Of Equation At M = 2 Anmentioning
confidence: 99%
“…Kudryashov and Sinelshchikov further extended their model in Ref. [29], where small effects of liquid compressibility and surface tension were considered, leading to third-and fourth-order partial differential equations. In parallel, Kanagawa et al [30] proposed a systematic derivation of nonlinear equations in bubbly liquids, based on parameter scaling.…”
Section: Introductionmentioning
confidence: 99%